2020
DOI: 10.1097/mca.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cardiac injury in COVID-19 patients with and without coronary artery disease

Abstract: Objective COVID-19 is a disease with high mortality, and risk factors for worse clinical outcome have not been well-defined yet. The aim of this study is to delineate the prognostic importance of presence of concomitant cardiac injury on admission in patients with COVID-19. Methods For this multi-center retrospective study, data of consecutive patients who were treated for COVID-19 between 20 March and 20 April 2020 were collected. Clinical characteristics, laboratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 21 publications
4
66
1
1
Order By: Relevance
“…The sMVAP index proves to be a practical OSAHS screening tool [ 3 ], including parameters such as age, gender, and BMI that only need to be extracted from the patient's electronic medical record. In this current study, the increased D-dimer and history of coronary heart disease were associated with poor prognosis, reflecting the direct effect of patients' coagulation function and cardiac dysfunction on mortality, consistent with previous reports [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The sMVAP index proves to be a practical OSAHS screening tool [ 3 ], including parameters such as age, gender, and BMI that only need to be extracted from the patient's electronic medical record. In this current study, the increased D-dimer and history of coronary heart disease were associated with poor prognosis, reflecting the direct effect of patients' coagulation function and cardiac dysfunction on mortality, consistent with previous reports [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously reported that troponin levels are higher and troponin elevations more common among non‐survivors with COVID‐19 2,8‐11 . A recent multi‐center retrospective study including 607 hospitalized patients with COVID‐19, found elevated troponin independently predicting mortality in patients with or without coronary artery disease, similar to our report 11 . These reports, along with our cohort, reveal a strikingly consistent rate of myocardial injury on admission among these patients‐about 20% to 25% despite a variable incidence of confounding factors like pre‐existing cardiac disease or renal disease.…”
Section: Discussionsupporting
confidence: 90%
“…Evaluation of increased CRP showed that baseline level over 10 , p = 0.001, I 2 = 14.7%, respectively), however, the analysis regarding the threshold of 50 mg/L was not significant, which makes these results inconsistent. In case of intensive care Fig.…”
Section: Odds Ratiosmentioning
confidence: 90%